Public-Private Wage gap in Australia: Variation Along the Distribution - Liu, A; Cai, L (My University, 2008)
Previous research on public-private wage differentials in Australia is scarce and has focused on the central parts of the conditional wage distribution. Using the first six waves of the Household, Income and Labour Dynamics in Australia (HILDA) survey, this study applies quantile regression models to examine whether the sectoral wage effect varies along the wage distribution. For females, we find public sector wage premiums for almost the entire wage distribution and the premiums are relatively stable except at the extremities of the distribution. For males, the premiums decrease monotonically and are negative for the top half of the conditional wage distribution. The decomposition results show that the observed differences in individuals and job characteristics account for a substantial proportion of the overall sectoral wage gap.
Centre for Economic Policy Research, the Australian National University, Discussion Paper .
CEPR Discussion Papers
Keywords: Finance -- Income (Salary and Wages); Employment -- Labour Markets; Employment; Finance; Labour market; Learning, education and training; Learning, education and training; Employment and unemployment